2021
DOI: 10.1002/adom.202101538
|View full text |Cite
|
Sign up to set email alerts
|

Impurity‐Induced Robust Trionic Effect in Layered Violet Phosphorus

Abstract: such as the strong room-temperature PL and abundant valley-selective excitation of excitonic states in transition metal dichalcogenides (TMDs). [2,[4][5][6][7] Besides, a neutral exciton can capture an additional electron (e) or hole (h) to form a correlated threeparticle state (e-e-h or h-e-h), known as a trion (T), in the presence of excess carriers. [8] It has been demonstrated that trionic effect can strongly affect the PL properties of 2D materials through controlling the excess carriers' population. [9][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…In the last few years, researchers have prepared VP-related nanomaterials and conducted a lot of investigations on their optoelectronic properties. For examples, Zhang et al 4 reported a high yield synthesis of VP crystals; Zhao et al 5 synthesized VP quantum dots and studied their fluorescence properties; Zhang et al 2 investigated the band alignment of few-layer violet phosphorene; Zhang et al 6 explored the phonon properties of VP single crystals; Zhang et al 7 demonstrated the friction anisotropy of violet phosphorene; and Li et al 8 reported the impurity-induced robust trionic effect in layered VP. It is noteworthy that the nonlinear optical properties of BP have been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, researchers have prepared VP-related nanomaterials and conducted a lot of investigations on their optoelectronic properties. For examples, Zhang et al 4 reported a high yield synthesis of VP crystals; Zhao et al 5 synthesized VP quantum dots and studied their fluorescence properties; Zhang et al 2 investigated the band alignment of few-layer violet phosphorene; Zhang et al 6 explored the phonon properties of VP single crystals; Zhang et al 7 demonstrated the friction anisotropy of violet phosphorene; and Li et al 8 reported the impurity-induced robust trionic effect in layered VP. It is noteworthy that the nonlinear optical properties of BP have been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These high-frequency intratube modes were due to the majorly localized bond stretching and bending. Furthermore, the complex Raman spectrum reflects a large density of phonon states in VP crystals, indicating a strong light–matter interaction . X-ray diffraction (XRD) analysis was also conducted using an x-ray diffractometer (Ultima IV) to identify the crystallinity and structure of the as-prepared VP nanosheets.…”
Section: Methodsmentioning
confidence: 99%
“…The excellent resistance to bending deformation is critical for ensuring the compatibility of the material and the performance and service life of the related optoelectronic devices. Additionally, Li et al reported that VP has a strong trionic effect and high trionic binding energy of ∼109 meV at room temperature (higher than that of other common 2D materials, such as graphene and transition-metal sulfides, whose trionic binding energy is <50 meV), confirming that it is a superior system for investigating the interaction between light and matter …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In 2020, violet phosphorus (VP) was successfully synthesized as a new two-dimensional material 20 with a more stable phosphorus isomer than that of black phosphorus. 21 Because VP possesses many unique properties, 22−24 it has been widely studied in catalysts, 25,26 sensors, 27 and optoelectronic fields 28,29 and has presented great potential for applications in the field of tribology. 30 However, few studies have reported its performance in the macroscale friction field, and VP is expected to replace the other 2D materials as a better lubricant additive.…”
mentioning
confidence: 99%